The Role And Importance of Using the Experience of Foreign Modern Cinematographers in the Development of Uzbek Cinematography - Orif Rashidovich Rakhimdjanov (Zien Journals, 2022)
This article discusses the role of the global film industry in Uzbek cinema and the need to use the experience of world cinema in it in parallel with the rapid development of the world. The article describes the equipment and tools that are widely used in the modern world, as well as methods that will help develop the future of our domestic cinema through the study of the experience of masters. The article also gives an insight into aspects of the global film industry
Keywords: cinema; cinematography; film industry; cinematographer